Transitivity and non-uniform subjecthood in agreement attraction. - Yoo, Myung Hye; Tollan, Rebecca (Memory & Cognition, 2024)
Research on human language converges on a view in which a grammatical "subject" is the most saliently encoded entity in mental representation. However, subjecthood is not a syntactically uniform phenomenon. Notably, many languages encode morphological distinctions between subjects of transitive verbs (i.e., verbs that require an object) and subjects of intransitive verbs. We ask how this typological pattern manifests in a language like English (which does not morphologically signal it) by examining the "distinctiveness" of transitive versus intransitive subjects in memory during online sentence processing. We conducted a self-paced reading experiment that tested for "attraction" effects (Dillon et al., Journal of Memory and Language, 69(2), 85–103, 2013; Wagers et al., Journal of Memory and Language, 61, 206–237, 2009) in the processing of subject-verb number agreement. We find that transitive subjects trigger attraction effects, but that these effects are mitigated for intransitive subject attractors (independently of the number of other noun phrases present in the intervening clause). We interpret this as indicating that transitive subjects are less distinctive and therefore less representationally salient than intransitive subjects: This is because a transitive subject must compete with another clause-mate core argument (i.e., a direct object), which draws on resources from the same pool of memory resources. On the other hand, an intransitive subject minimally only competes with a non-core argument (i.e., an oblique noun phrase); this consumes fewer memory resources, leaving the subject to enjoy greater spoils.